Application of surgical navigation in styloidectomy for treating Eagle’s syndrome - Dou G; Zhang Y; Zong CL; Chen YL; Guo YX; Tian L (Dove Medical Press, 2016)
Geng Dou,1 Yu Zhang,1 Chunlin Zong,2 Yuanli Chen,2 Yuxuan Guo,2 Lei Tian2 1The First Brigade of Students, 2State Key Laboratory of Military Stomatology, National Clinical Research Center for Oral Diseases, Shaanxi Key Laboratory of Oral Diseases, Department of Cranio-facial Trauma and Orthognathic Surgery, School of Stomatology, The Fourth Military Medical University, Xi’an, People’s Republic of China Purpose: The present study aimed to evaluate the feasibility, accuracy, and clinical effect of intraoperative navigation for resection of elongated styloid process (ESP) in Eagle’s syndrome.Patients and methods: Twelve patients with Eagle’s syndrome with clinically and radiologically established diagnoses of ESP were included in this study. Preoperatively, all patients accepted three-dimensional computed tomography scan, and their skulls’ digital imaging and communications in medicine data were inputed into the navigation system workstation to make a virtual surgical plan in advance. During surgery, the intraoperative navigation was performed to excise the ESP accurately for both intraoral (without tonsillectomy) and extraoral approaches following the virtual plan. Postoperatively, the amount of bleeding, duration of operation and hospitalization, and the length of resected styloid process (SP) were measured and compared with those cases that had traditional styloidectomy without the help of surgical navigation (SN). A simple visual analog scale questionnaire was also used to assess patients’ satisfaction and the surgery effect after 3 months.Results: In total, 17 SPs from 12 patients were precisely resected by intraoral parapharyngeal approach and small cervical approach with the aid of SN. No severe complications occurred in any patients. The length of resected SPs was 21.93±14.26 mm. The average amount of bleeding and duration of operation were 22.50±8.54 mL and 40.35±11.81 minutes, respectively, which were all less than with traditional styloidectomy. The visual analog scale analysis showed that the discomfort in all patients was relieved, while ten patients’ symptoms were improved greatly, and two patients had some improvement.Conclusion: The higher accuracy of surgery, lesser amount of bleeding, decreased duration of surgery and hospitalization, absence of complications, and improved subjective symptoms indicated that SN is an effective and minimally invasive surgical procedure suitable for resection of ESP for treating Eagle’s syndrome. Keywords: elongation of styloid process, intraoperative navigation, oral and maxillofacial surgery, computer-aided surgery